Identification of Conjugated Linoleic Acid in Milk Fermented by Probiotics Originating in the Gastrointestinal Tract - Kafaah Estancia; Widodo Widodo (Buletin Peternakan, 2019)
One of the benefits of probiotics is their ability to synthesize conjugated linoleic acid (CLA) as a functional bioactive compound. The objective of this study is to identify CLA synthesized in milk fermented with the probiotic Lactobacillus casei strain AP and Lactobacillus casei strain AG as starter cultures. Fermented milk products were analyzed using gas chromatography-mass spectrometry (GC-MS) to characterize the CLA formed. The result of GC-MS in milk fermented using Lactobacillus casei strain AG was detection of a CLA compound with a retention time of 41.467, whereas in milk fermented using Lactobacillus casei strain AP, linoleic acid, but not CLA, was detected.